3D modelling system for diagnosis and treatment planning of prostate cancer - Appan Kumaresan Esaki (2008)
An apparently rising incidence of and mortality from prostate cancer coupled with an increasing life expectancy and an expanding population at risk have made this neoplasm a major medical and socioeconomic problem. Adenocarcinoma of the prostate is estimated to be among the most common malignancies diagnosed in men all over the world. It is the second cause of male cancer death in USA and fifth in Singapore. For this reason, the study of prostate cancer and development of improved treatment methods takes on an almost urgent significance.